PENGARUH PENYAJIAN LAPORAN KEUANGAN DAN AKSEBILITAS KEUANGAN DAERAH TERHADAP AKUNTABILITAS PENGELOLAAN KEUANGAN DAERAH KABUPATEN ACEH UTARA - M. Lutfi Al Fahmi; Zulkarnaini Zulkarnaini; Fauzan Fauzan; Bobby Rahman; Maulidin Maulidin; Athailah Athailah (Sekolah Tinggi Ilmu Ekonomi Wiyatamandala, 2023)
This literatur target to examine the impact of regional financial accessibility and the presentation of financial reports on the accountability of regional financial management in the North Aceh Region. The researchers employed purposive sampling to collect primary data from a sample of 104 individuals. Multiple linear regression analysis and standard assumption tests were conducted to assess the relationship between the independent variables and the dependent variable. The findings indicate that the accountability of regional financial management in the North Aceh Region is significantly influenced by the accessibility of regional financial resources. However, the introduction of budget summaries does not have a substantial impact on the accountability of territorial financial management in the same region. Furthermore, the study demonstrates that the availability of regional finance and the introduction of financial reports significantly affect the accountability of regional financial management in the North Aceh Region.